1975
DOI: 10.1002/hlca.19750580817
|View full text |Cite
|
Sign up to set email alerts
|

A 13C‐NMR. Study of cis‐trans Isomeric Vitamins A, Carotenoids and Related Compounds

Abstract: The 1H-decoupled 1sC-NMR. spectra of 35 all-trans, 17 mono-cis vitamin A compounds (acetates, alcohols, aldehydes, acids and esters) and of one 11,13-di-cis compound (11,13di-cis rctinol) are reported. Included in this investigation are desmeth yl-, dcsmethylethyl, and aryl-vitamin A analogues and others as well as 30 reference compounds of smaller molecular weight. Furthermore, the 13C-NMR. spectra of 23 p-apo-and other carotenoids were studicd. A complete assignment of the signals of all 106 compounds to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
0
8

Year Published

1976
1976
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(59 citation statements)
references
References 18 publications
11
40
0
8
Order By: Relevance
“…The 300-MHz 'H nmr spectra of la,b are identical to those described by Patel (25) except for the additional '"-'H coupling constants as shown in Table 1. The 75.5-MHz "C nmr spectra of la,b display the enriched signals and are further identical to those described by Englert (16) except for the additional 1qC-'3C coupling constants as shown in Table 2; ms: l a and l b m / z 285 (M'): level of "C enrichment calculated from the mass spectra: 93%.…”
Section: (D ' J ( C~-(~-c H~) )supporting
confidence: 74%
See 1 more Smart Citation
“…The 300-MHz 'H nmr spectra of la,b are identical to those described by Patel (25) except for the additional '"-'H coupling constants as shown in Table 1. The 75.5-MHz "C nmr spectra of la,b display the enriched signals and are further identical to those described by Englert (16) except for the additional 1qC-'3C coupling constants as shown in Table 2; ms: l a and l b m / z 285 (M'): level of "C enrichment calculated from the mass spectra: 93%.…”
Section: (D ' J ( C~-(~-c H~) )supporting
confidence: 74%
“…They display one strong single line due to the labelled carbon atom at the chemical shift value known from the natural abundance I3C nmr spectrum of unmodified retinal (16 Table 2.…”
Section: Synthesis and Spectroscopic Characterizationmentioning
confidence: 99%
“…As shown in Table 1, the shift difference between the all-trans and 13-cis protonated Schiff bases in solution is a mere 1.4 ppm at the C-14 position, in accordance with Englert (25), who reported changes of 1-2 ppm for seven retinal derivatives on 13-cis isomerization. Similarly, isomerization about the C-9, C-10 and C-11, C-12 double bonds causes only small changes in the shifts of the carbons of the isomerized bond itself (25)(26)(27), about an order of magnitude too small to account for the change observed here. The nature of the Schiff base counterion might also be expected to affect the isotropic shift of protonated Schiff bases at the C-14 position.…”
Section: Methodsmentioning
confidence: 52%
“…Specifically, Englert (25) shows upfield shifts of -6-8 ppm at C-12 on going from all-trans to 13-cis isomers in seven retinal derivatives, and at C-8 in the case of C-9, C-10 isomerization. Recently, we showed that the C-12 position of N-(13-cis-retinylidene)propyliminium trifluoroacetate has a shift 9.1 ppm upfield of the all-trans-derivative (15), a shift actually larger than any observed by Englert.…”
Section: Methodsmentioning
confidence: 97%
“…data on fifteen carotenoid end groups and several others have been recorded since (Ref. 2). A major problem with this technique is the rather large samples required, although modern instruments using super conducting magnets have reduced the quantity required.…”
Section: Nm R Spectroscopymentioning
confidence: 99%